2013
DOI: 10.15580/gjas.2013.3.030613516
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Analysis of Vegetative-Stage Drought Tolerance in Cowpea

Abstract: The continued improvement in the yield of cowpea for the semi-arid regions where it is a dominant crop will record rapid progress if the genetic basis for yield under different moisture regimes is better understood. This study investigated the genetic combining abilities and heterosis for grain yield, yield components, flowering and biomass production among diallel hybrids derived from nine cowpea genotypes. Results showed that moisture stress significantly reduced grain yield, biomass production, and number o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 11 publications
3
18
0
1
Order By: Relevance
“…Improvement for these traits therefore requires a recurrent selection procedure that allows for favorable gene recombination in later generations before a final selection is made. Similar results on moderate to low narrow sense heritability estimates for grain yield, 100 seed weight and number of pods per plant were reported by Alidu et al (2013). However, these results contradicted with Chiulele (2010) findings, possibly due to the differences in the population studied, multilocationality of the study as Chiulele's study was conducted across locations while this study was done in one location.…”
Section: Heritability and Combining Abilitysupporting
confidence: 73%
See 1 more Smart Citation
“…Improvement for these traits therefore requires a recurrent selection procedure that allows for favorable gene recombination in later generations before a final selection is made. Similar results on moderate to low narrow sense heritability estimates for grain yield, 100 seed weight and number of pods per plant were reported by Alidu et al (2013). However, these results contradicted with Chiulele (2010) findings, possibly due to the differences in the population studied, multilocationality of the study as Chiulele's study was conducted across locations while this study was done in one location.…”
Section: Heritability and Combining Abilitysupporting
confidence: 73%
“…Gene action studies conducted elsewhere have reported the predominance of additive genetic effects over non-additive genetic effects in controlling yield components such as days to flowering, number of seeds per pod, number of pods per plant and hundred seed weight (Chiulele, 2010;Romanus, 2008). Non-additive genetic effects were, however, more important for seed yield (Chiulele, 2010;Alidu et al, 2013). Thus, information regarding combining ability and nature of gene action governing the inheritance of desirable traits are basic requirements for breeding high yielding drought tolerant cowpea genotypes.…”
Section: Introductionmentioning
confidence: 99%
“…Cowpea is sensitive to soil moisture stress during the vegetative and reproductive growth stages [9]. Drought stress during flowering and pod filling impacts negatively on flower development, pollination, pod setting and grain filling leading to reduced number of pods per plant, reduced seed weight and low seed yield [10].…”
Section: Introductionmentioning
confidence: 99%
“…The additive gene action was also identified as more important in the inheritance of yield related traits, 100-seed weight, number of seeds per pod, Normalized Difference Vegetation Index (NDVI) measured at three different growth stages and the number of pods and seeds per plant under drought stress. High GCA effects were also reported for hundred seed weight, pod per plant and grain yield in cowpea progenies grown under water stress (Carvallo et al, 2012;Alidu et al, 2013). Information on gene action controlling drought tolerance, yield and its associated traits is scarce in cowpea.…”
Section: Gene Action Of Drought Tolerance In Cowpeamentioning
confidence: 99%